State-of-the-art efficiency determination of a wind turbine drivetrain on a nacelle test bench - H. Zhang; P. Weidinger; C. Mester; Z. Song; M. Heller; A. Dubowik; B. Tegtmeier; K. Eustorgi (Wind Energy Science)
The efficiency of wind turbine drivetrains is a topic of great interest for both the wind energy industry and the academic community. With the developing maturity of this technology and the increasing pressures to reduce costs, the importance of drivetrain efficiency has grown. However, measuring the mechanical input power and the electrical output power with sufficient accuracy is very challenging due to the high power level of the drivetrain. In the project known as WindEFCY, state-of-the-art measurement and calibration instruments are used to determine the drivetrain efficiency of a direct drive wind turbine on the nacelle test bench called DyNaLab. This paper discusses the test configuration applied for this work as well as the instrumentation of the measurement systems used. It further presents the results from two tests of different types to demonstrate the process of efficiency determination, the analysis of uncertainty and the consequent comparability of the tests. Within the paper's scope of study, an uncertainty level of approximately 0.7 % is achievable when measuring drivetrain efficiency. Details and recommendations concerning data processing and uncertainty analysis are also given in the paper.